Knowledge regarding HIV/AIDS among Armed Police Force – Banke, Nepal - Roy, Roshan Kumar; Roy, Deepak Kumar; Ghimire, Sabal; Bist, Aayush (Journal of Kathmandu Medical College, 2018)
Background: A global pandemic threat HIV/AIDS is a matter of concern for developing countries like Nepal. The first case was identified in July 1988 and later became epidemic and then concentrated epidemic among risk group for HIV. Several studies reflected that HIV is associated with many factors among which literacy rate and socio-economic conditions hold the highest rank. Armed Police Force of Nepal are generally with less educational background and very few with higher educational status are at higher level. Thus knowledge regarding HIV/AIDS among this group needs to be assessed. Objectives: The overall objective of our study was to assess knowledge regarding HIV/AIDS among Armed Police Force in Banke, Nepal. Methodology: A cross-sectional descriptive study with population size of 295 Armed Police Force was performed which covered the entire population of an Armed Police Force camp in Banke starting from 18th June to 27th July, 2018. A pretested questionnaire containing structural, semi-structural and open ended questions were made as data collection tool. All the soldiers in Armed Police Force camp were interviewed after receiving consent as an ethical clearance. Results: All 295 armed police forces of our study were aware about HIV/AIDS mainly via mass media (83%). One hundred and fifty eight respondents still did not know about availability of its treatment. Misconception about its complete cure and vaccination was seen in 23 (7.79%) and 61 (20.67%) respondents respectively. Two hundred and one respondents were found knowing about the free health services by government. 287 (97.28%) respondents knew certain things about prevention. Twenty four respondents admitted of having multiple sex partners and only 19 (79.16%) among them used preventive measure. Conclusion: Though all the respondents of our study had known about HIV/AIDS, still they had misconception regarding its treatment and prevention. Many respondents did not even know about the free health services of government. Few of them still do not use any preventive measure.